2019
DOI: 10.1021/acs.jafc.9b06630
|View full text |Cite
|
Sign up to set email alerts
|

Untargeted Metabonomics of Genetically Modified Cows Expressing Lactoferrin Based on Serum and Milk

Abstract: Metabolites of serum and milk from genetically modified (GM) cows and contrast check (CK) cows were comparatively investigated. Serum and milk were collected from genetically modified (GM) cows and contrast check (CK) cows, and then, they were analyzed using ultraperformance liquid chromatography–mass spectrometry (UPLC–MS) and gas chromatography–mass spectrometry (GC–MS). Although the level of some blood biochemical indexes for GM cows was shifted up or down, they were generally in normal physiological condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Though there is a core milk metabolome, exploring differences in the metabolites of human milk and comparing the metabolites to whole bovine milk may identify potential pathways to deepen our understanding of the protective mechanisms of human milk for human infants. Moreover, 67.7% of metabolites detected in our study have been previously identified in untargeted metabolomics studies, including 46 related to amino acid metabolism [8,[45][46][47][48][49][50][51][52][53][54][55][56][57][58][59], 23 carbohydrates [46,47,[50][51][52][53]55,[59][60][61][62], 11 co-factors and vitamins [46,47,52,55,61,63], 26 nucleotides [45][46][47][48][49][50]54,55,57,58,[60][61][62], and 21 xenobiotics [...…”
Section: Previous Workmentioning
confidence: 71%
“…Though there is a core milk metabolome, exploring differences in the metabolites of human milk and comparing the metabolites to whole bovine milk may identify potential pathways to deepen our understanding of the protective mechanisms of human milk for human infants. Moreover, 67.7% of metabolites detected in our study have been previously identified in untargeted metabolomics studies, including 46 related to amino acid metabolism [8,[45][46][47][48][49][50][51][52][53][54][55][56][57][58][59], 23 carbohydrates [46,47,[50][51][52][53]55,[59][60][61][62], 11 co-factors and vitamins [46,47,52,55,61,63], 26 nucleotides [45][46][47][48][49][50]54,55,57,58,[60][61][62], and 21 xenobiotics [...…”
Section: Previous Workmentioning
confidence: 71%
“…In order to increase the production of FSH, insect cells and Pichia pastoris have been applied to prepare FSH. , However, FSH prepared by insect cells or Pichia pastoris was found to be different in the oligosaccharide structure when compared with natural FSH, which affected the glycosylation and bioactivity of FSH. The animal mammary gland bioreactors are used to produce a wide range of foreign proteins, which have natural protein post-translational modifications, including glycosylation, phosphorylation, and carboxylation. Preparation of human FSH or bovine FSH by mammary glands in mice and rabbits has been explored, , but the animals were found to suffer serious adverse side effects due to excessive FSH leakage into blood from mammary glands . It is of high importance to develop a better method to produce rhFSH in a large scale.…”
Section: Discussionmentioning
confidence: 99%
“…And it can amplify small differences in upstream gene and protein expression, and further in‐depth analysis of the metabolic pathways related to different metabolites can explain the mechanism of action of the research object (Wu et al., 2021 ). This technology has been widely used in food science (Chen et al., 2020 ), medicine (Wang, Zhang, et al., 2020 ; Wang, Chen, et al., 2020 ; Wang, Gong, et al., 2020 ; Wang, Jia, et al., 2020 ) and other fields. Nontargeted metabolomics can comprehensively and unbiasedly reflect the metabolic state of small molecules in organisms, which is conducive to the screening of biomarkers and the construction of dynamic metabolic networks in organisms (Wang, Zhang, et al., 2020 ; Wang, Chen, et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…This technology has been widely used in food science (Chen et al., 2020 ), medicine (Wang, Zhang, et al., 2020 ; Wang, Chen, et al., 2020 ; Wang, Gong, et al., 2020 ; Wang, Jia, et al., 2020 ) and other fields. Nontargeted metabolomics can comprehensively and unbiasedly reflect the metabolic state of small molecules in organisms, which is conducive to the screening of biomarkers and the construction of dynamic metabolic networks in organisms (Wang, Zhang, et al., 2020 ; Wang, Chen, et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%